2010
DOI: 10.3920/bm2009.0042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of beneficial attributes for phytate-degrading Pediococcus pentosaceus CFR R123

Abstract: In this study we have screened and selected potent phytate-degrading lactic acid bacteria (LAB), and evaluated their beneficial attributes. Around 60 LAB strains were isolated from several cereal- and pulse-based conventional fermented preparations. They were screened for their ability to degrade myo-inositol hexakisphosphate (IP6) by cobalt chloride qualitative staining method (plate assay). One of the cultures, Pediococcus pentosaceus CFR R123, was capable of degrading both calcium and sodium salts of phytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…These results differ from the previous report by Mourad and Nour-Eddine (2006) who found that L. plantarum strains isolated from olives have better survival rates at acidic pH than other bacteria strains. The reduction of survivability of LAB at low pH was also reported by Raghavendra, Rao, and Halami (2010), which demonstrates the survivability of Pediococcus pentosaceus CFR R123 (53%) and L. rhamnosus GG (55%) after incubation at pH 2.0 for 3 hours. The results indicate that the Lactobacillus strains could survive in the acidic stomach environment and reach the areas of beneficial activity (small intestine and colon).…”
Section: Strainmentioning
confidence: 86%
“…These results differ from the previous report by Mourad and Nour-Eddine (2006) who found that L. plantarum strains isolated from olives have better survival rates at acidic pH than other bacteria strains. The reduction of survivability of LAB at low pH was also reported by Raghavendra, Rao, and Halami (2010), which demonstrates the survivability of Pediococcus pentosaceus CFR R123 (53%) and L. rhamnosus GG (55%) after incubation at pH 2.0 for 3 hours. The results indicate that the Lactobacillus strains could survive in the acidic stomach environment and reach the areas of beneficial activity (small intestine and colon).…”
Section: Strainmentioning
confidence: 86%
“…This is in agreement with previous reports from other plant sources. Camacho et al (1991) reported that a strain of L. buchneri decreased PA by more than 55% in average, after 12 h of lupine flour fermentation and several P. pentosaceus strains from sourdough have been shown to exhibit PA degradation capacity on modified MRS agar medium (Raghavendra et al, 2010). Numerous studies have also reported L. plantarum strains to be phytase positive (Lopez et al, 2000;Songré-Ouattara et al, 2008;Sreeramulu et al, 1996;Tang et al, 2010) although more detailed studies revealed an extracellular dephosphorylating enzyme rather unspecific for sodium PA but with a high affinity to acetyl phosphate (Zamudio et al, 2001).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, from among 60 strains of LAB from cereal-and pulse-based fermented mixtures, P. pentosaceus CFR R123 not only significantly improved the availability of calcium but also reduced cholesterol and β-galactosidase levels. P. pentosaceus CFR R123 degraded 43% of phytate in one hour in an experiment designed by Raghavendra et al [54,55]. These phytatedegrading P. pentosaceus have potential as nutritive food additives [54,55].…”
Section: Promotion Of Mineral and Nutrient Utilizationmentioning
confidence: 99%